Analysis of the Physicochemical Characteristics of Distillery Wastewater at Habib Sugar Mills, Nawabshah - Jakhrani, N. H.; Mukwana, K. C.; Bhutto, M. A.; Mangi, D. M.; Hafeez, M. (Engineering, Technology & Applied Science Research, 2021)
The aim of this study is to perceive the level of significant physicochemical characteristics of Distillery Wastewater (DWW) at Habib Sugar Mills, Nawabshah, Pakistan. Five locations in the mill namely spent wash, digester tank, distillery, primary treatment, and secondary treatment were selected for analysis of pH, Total Dissolved Solids (TDS), Total Suspended Solids (TSS), and Chemical Oxygen Demand (COD) of the samples. The samples were taken on a weekly basis for four succeeding months, from January 2021 to April 2021 and the experiments were carried out in the laboratory by adopting standard procedures. The results revealed that the pH of the samples from spent wash was the lowest, whereas secondary treatment samples had the highest. On the contrary, the highest concentrations of TDS, TSS, and COD were found in the samples taken from the spent wash and the lowest from the secondary treatment. The pH values were found abruptly increasing in the digester tank due to the addition of calcium carbonate in the stream of wastewater after the spent wash. The COD concentration was found to rapidly decrease, from more than 106000mg/l in the spent wash to around 35000mg/l in the digester tank samples, and then to gradually decrease up to the final point of disposal. Overall, TDS, TSS, and COD values were higher during April, January, and February and lower during March. The level of pH was extremely low in the spent wash and did not meet the lower limits of standards and the other examined parameters exceeded the upper limits of WHO standards.